OWNERSHIP, FIRM SIZE DAN RASIO KEUANGAN TERHADAP EARNINGS MANAGEMENT - Muhammad Reza Fadhillah; Rudi Setiadi Tjahjono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to obtain empirical evidence and analyze the factors that influence earnings management. The independent variables used in this research are institutional ownership, leverage, firm size, firm age, growth, liquidity, profitability. The dependent variable used in this study is earnings management. The data collection method used in this study is a quantitative method using secondary data. The data used in this study are the annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. The research data was obtained through the Indonesia Stock Exchange website (www.idx.co.id). The technique used in sampling is by using purposive sampling method. The number of samples in this study were 71 companies with a total of 213 data. Hypothesis testing used in this study is multiple regression. The results of this study indicate that leverage, firm age, profitability has an effect on earnings management. Whereas institutional ownership, firm size and financial ratio which consist of growth and liquidity have no effect on earnings management.